THE CIVILIZATIONAL APPROACH TO STUDYING THE PHENOMENON OF RUSSIAN PRE-REVOLUTIONARY CHARITY - Pokotilova, Tatyana; Ulibina, Lubov; Sinkov, Dmitry; Khalilovа Khalida; Panarina, Elena (Revista Inclusiones, 2020)
The article is devoted to the issue of studying Russian pre-revolutionary charity as one of the phenomena in the history of Russia, which evolution largely determined the specifics of its culture and the hierarchy of social values. It is shown that relying on the civilizational approach, which suggests that culture can be considered as a social way of human activity and society, charity must be studied as a particular sociocultural phenomenon. In its evolution charity went from being proclaimed a moral obligation by the church and gaining recognition by the state as one of the mechanisms for stabilizing social relations in the context of socioeconomic inequality to a cultural tradition that significantly contributed to the emergence and growth of legal forms of civic activity in a country with an autocratic nature of power.